Legal Aspects and Role of Ojk In Bank Digital by Digital Banking Services During Post-Covid 19 Pandemic in Indonesia - Sulistyandari; Sutrisno, Putri Ayu (Journal of Law and Sustainable Development, 2023)
Objective: The purpose of this research is to analyze the implementation of bank digital by digital financial services that are able to maintain bank secrecy and personal data security; and to analyze the application of prudent banking principles in the implementation of bank digital by digital services in Indonesia; and it also aim to analyze the role of the OJK in regulating and supervising Bank Digital by digital services post Covid 19 pandemic.